Deprescribing medicines in an intensive care unit of a university hospital from Ceará - Ana V. OLIVEIRA; Renata V. CORTEZ; Elana F. CHAVES; Liana M. MAGALHÃES; Romênio N. BORGES; Amanda M. CONCEIÇÃO; Cinthya C. ANDRADE; José M. ALCÂNTARA-NETO; Hilris R. SILVA (Sociedade Brasileira de Farmácia Hospitalar e Serviços de Saúde, 2022)
Objectives: To evaluate the pharmaceutical deprescription recommendations made to patients hospitalized in an adult clinical Intensive Care Unit (ICU). Methods: This is a cross-sectional, descriptive, and quantitative study developed with pharmaceutical recommendations for drug deprescription, in the adult ICU of a university hospital in Fortaleza - CE, from 2017 to 2018. Data from patients and recommendations were collected from patient records. The acceptability of the recommendations was measured from the visualization of the suggested alteration in 24 hours. The drugs included in the recommendations were categorized according to the Anatomical Therapeutic Chemical (ATC) and Potentially Dangerous Drug (MPP) classifications. The data were compiled and analyzed using the Microsoft Office Excel® 2013 software. Results: A total of 388 recommendations were made for the non-prescription of medications to 210 adult patients who were mostly male (58%) and with a mean age of 56 years. ± 16.8. The acceptability of the recommendations was 93.3% (n=362) and the average number of medications not prescribed per patient was 1.7 ± 0.7, all of which were abruptly discontinued. Problems related to deprescription were mainly prescription of unnecessary drugs (77.6%) contraindicated drugs (8.0%) and therapeutic duplicity (5.1%). The most frequent therapeutic classes are antibacterials for systemic use (11.3%), ophthalmic (20.8%) and medicines for functional gastrointestinal disorders (9.5%). The main drugs not prescribed were hypromellose eye drops + dextran (9.6%), bromopride (6.9%) and injectable potassium chloride (5.8%), the latter being considered an MPP. The class most associated with non-acceptance of deprescription other than corticosteroids is systemic use (23.1%). Conclusion: This study showed a high level of acceptance of deprescription recommendations, especially among antibacterials for systemic use. Injectable potassium chloride, considered an MPP, ranked third overall in terms of non-prescription. Future studies should evaluate the impact of deprescription recommendations on morbidity and mortality in the ICU and on the reduction of hospital costs.